2017
DOI: 10.24193/adn.10.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Attitude towards STEM Education

Abstract: STEM is the acronym of Science, Technology, Engineering, and Mathematics fields. STEM education refers both to teaching and learning in the above-mentioned disciplines, but especially to teaching and learning a new discipline based on the integration of Science, Technology, Engineering, and Mathematics. The present survey aims to investigate the opinion of a sample of 110 respondents, students from Romanian universities, taking into account: a) their experience in STEM fields during high school studies; (b) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 7 publications
(7 reference statements)
2
11
0
7
Order By: Relevance
“…Çocuklar ile birlikte, sınıfta çeşitli materyalleri kullanarak belirlenen uzaklığa/yüksekliğe ulaşmak üzere hazırlanacak bir sistem kurmak planlanabilir. Verilen iki örnek problem durumu ve gerçek yaşam durumlarından yola çıkılarak ele alınabilecek sayısız problem aracılığıyla; çocuklar gerçek yaşam bağlamında ele alabilecekleri yöntemleri (sorgulamaya dayalı öğrenme ve değerlendirme yöntemleri) deneyimleyerek eleştirel ve bilimsel düşünme becerilerini geliştirebilir ve bilimle bütünleşmiş bir bakış açısı oluşturur (Popa ve Ciascai, 2017). Çocuklar bu süreçte; STEM eğitimi aracılığıyla problem çözme, bilimsel araştırmalar yürütme, matematik uygulamaları yapma ve teknolojik tasarımlar oluşturma konularında deneyim kazanabilirler (Sanders, 2009).…”
Section: Erken çOcukluk Döneminde Stem Eğitimi Anlayışıunclassified
See 1 more Smart Citation
“…Çocuklar ile birlikte, sınıfta çeşitli materyalleri kullanarak belirlenen uzaklığa/yüksekliğe ulaşmak üzere hazırlanacak bir sistem kurmak planlanabilir. Verilen iki örnek problem durumu ve gerçek yaşam durumlarından yola çıkılarak ele alınabilecek sayısız problem aracılığıyla; çocuklar gerçek yaşam bağlamında ele alabilecekleri yöntemleri (sorgulamaya dayalı öğrenme ve değerlendirme yöntemleri) deneyimleyerek eleştirel ve bilimsel düşünme becerilerini geliştirebilir ve bilimle bütünleşmiş bir bakış açısı oluşturur (Popa ve Ciascai, 2017). Çocuklar bu süreçte; STEM eğitimi aracılığıyla problem çözme, bilimsel araştırmalar yürütme, matematik uygulamaları yapma ve teknolojik tasarımlar oluşturma konularında deneyim kazanabilirler (Sanders, 2009).…”
Section: Erken çOcukluk Döneminde Stem Eğitimi Anlayışıunclassified
“…Örneğin, Kazakoff, Sullivan ve Bers ( 2013) 'e göre, robotik ve programlama etkinliklerine katılan çocuklar sıralama ile ilgili becerilerini bu etkinlikler yoluyla geliştirirler. STEM eğitim anlayışı öğrenme ortamlarında kullanılmakta olan materyaller kapsamı; yazılımlardan robotlara, bilgisayarlardan artık materyallere oldukça geniş bir çerçevede olsa da, etkili bir STEM eğitim modelinin doğasına (öğrencilerin erken deneyimleri ve ilgi alanlarını kullanır, önceden var olan bilgisini ve becerilerini [bildikleri] tanımlar ve kullanır, onları dahil eder, bilimsel etkinliklere olan ilgisini sürdürür ve onları bilimsel etkinliklere katılmaya motive etmek için tasarlanmış deneyimler sunar) yakın çerçevede kalmasını sağlayacak miktarda olması önemlidir (Capraro ve Slough, 2013;Popa ve Ciascai, 2017).…”
Section: Erken çOcukluk Döneminde Stem Eğitimi Anlayışıunclassified
“…Not only is there relatively more investment, but also there is a great pressure on ordinary schools with relatively tight funds, and teachers'teaching thinking is often limited by equipment, which can not really play the core role of STEM curriculum. Especially for the graduates who are under great pressure to enter higher education, they can not spare a lot of time for STEM courses [5] .…”
mentioning
confidence: 99%
“…Many countries who are keeping pace with technological or engineering developments and innovations, either to strengthen the economy as well as to protect from threats of other countries, or to remain or become leaders in the rapidly changing and expanding global economy, have taken steps to enrich and improve the STEM curriculum, STEM educational policy and STEM-related workforce development [3]. Hence, numerous STEM-related researches can be found focusing either on teachers [4], [5], [6], [7], [8] or students, in which the latter commonly involved school students [1], [9], [10], [11] and college or university students [12], [13], [14], [15].…”
mentioning
confidence: 99%
“…Thus, it is not surprising to find many researchers discussed heavily on academic preparedness and students' interest in STEM [18], as well as other supporting factors such as STEM competitions [8], out-of-school STEM activities [19], [20] STEM pre-knowledge [1] and other STEM-based programs [11], [21] which highly likely encourage the students' pursuit of STEM fields in college. Some researches were also carried out to investigate students' or youth's attitude towards STEM fields [10], [14], [22], Most of them reported moderately to highly positive attitudes. Moreover, there were also researchers that relate the attitude or interest with specific gender, such as Sahin et al [15] who found that males were more likely to choose a STEM major in college than females, which contradicted with Mau et al [13] who found that female students were more likely than male students to major in STEM field of studies.…”
mentioning
confidence: 99%